The Cultural Preaching Values of The Gayo Tradition Melengkan in Aceh - Marhamah, Marhamah; Fauzi, Fauzi; Rahmad, Rahmad (UIN Maulana Malik Ibrahim Malang, 2024)
The delivery of Islamic preaching can be effectively conducted through cultural approaches, such as the Gayo tradition of melengkan in Aceh. This tradition involves delivering speeches at wedding ceremonies using metaphorical sentences that embed Islamic messages. It serves as a valuable means of preaching and merits preservation. However, the tradition faces challenges due to the declining number of people skilled in the art of melengkan. It is hoped that local government policies will support training the next generation in the art of melengkan to prevent this tradition from becoming extinct. This research aims to analyze the forms and preaching values within the tradition, employing a descriptive qualitative research method. Data collection is conducted through interviews with key informants, including performers of melengkan, traditional leaders, and community figures from the Gayo community. Observations of traditional wedding ceremonies and analysis of melengkan speech texts are supplemented with other literature. The research findings indicate that the cultural preaching messages in melengkan include informative, persuasive, and coercive types. The values embodied within these messages encompass beliefs, worship or Sharia, and morality. Further studies could explore broader applications of cultural preaching values in multicultural settings worldwide, offering a model for other regions with similar cultural and religious dynamics. Penyampaian dakwah Islam dapat dilakukan secara efektif melalui pendekatan budaya, seperti tradisi melengkan di Aceh. Tradisi ini melibatkan penyampaian pidato dalam upacara pernikahan menggunakan kalimat metaforis yang menyertakan pesan-pesan Islam. Ini merupakan sarana berharga untuk berdakwah dan layak untuk dilestarikan. Namun, tradisi ini menghadapi tantangan karena menurunnya jumlah orang yang terampil dalam seni melengkan. Diharapkan kebijakan pemerintah daerah akan mendukung pelatihan generasi berikutnya dalam seni melengkan untuk mencegah kepunahan tradisi ini. Penelitian ini bertujuan untuk menganalisis bentuk dan nilai-nilai dakwah dalam tradisi tersebut, menggunakan metode penelitian kualitatif deskriptif. Pengumpulan data dilakukan melalui wawancara dengan informan kunci, termasuk pelaku melengkan, pemimpin tradisional, dan tokoh masyarakat dari komunitas Gayo. Observasi upacara pernikahan tradisional dan analisis teks pidato melengkan dilengkapi dengan literatur lainnya. Temuan penelitian menunjukkan bahwa pesan dakwah budaya dalam melengkan mencakup tipe informatif, persuasif, dan koersif. Nilai-nilai yang terkandung dalam pesan-pesan ini mencakup kepercayaan, ibadah atau Syariah, dan moral. Studi lanjutan bisa mengeksplorasi aplikasi luas nilai-nilai dakwah budaya di lingkungan multikultural di seluruh dunia, menawarkan model untuk wilayah lain dengan dinamika budaya dan agama yang serupa.